Konstruksi Keindonesiaan Dalam Film Tjokroaminoto - Ahmad Toni (Avant Garde, 2017)
This study uses critical discourse analysis method that aims to reveal the meaningof Indonesian keynthones in Tjokroaminoto Guru Bangsa film. The results showthat the representation of meaning at Indonesian level at the text level is arepresentation of the dominance of ethnic or racial tribes of Europe and Arabiaand subordinan tribes or races of Javanese, Chinese, Sundanese and do not havecitizenship. At the messo level the purpose of the film production system is thegoal of Tjokroaminoto's historical reconstruction based on the spirit of Islam asthe basis for the struggle. At the macro level shows the construction of nationalleadership is a rational effort in order to fulfill party politics based on the spirit ofkeindonesiaan. Keindonesiaan is the essence of the teachings of cultural Islamthat upholds human values in order to realize the concept of hijra or civil societyin Indonesia.